Evaluation of the chemical profile and antioxidant and toxicological potential of essential oils from Baccharis trimera samples sold in sachets (Research, Society and Development, 2022)
The bitter carqueja (Baccharis trimera) is widely used in alternative and herbal medicine. The essential oil components of its leaves could be included among the most important active principles of this herb and some of them can also be used as chemical markers of the species. Therefore, the aim of the present study is to establish the chemical composition and evaluate the toxicological potential and antioxidant capacity of essential oils from carqueja samples commercialized in Rio de Janeiro city as sachets, comparing these results with those obtained for essential oils classified as reference for this species. The essential oils from these sachet samples were isolated by hydrodistillation and analyzed by chromatographic techniques (GC/FID and GC/MS), spectrophotometric techniques (DPPH) and by the Artemia salina test. In the present study, 41 compounds were identified in the essential oils analyzed. Terpenic compounds were the majority and only carquejil acetate, palustrol, spathulenol and β-eudesmol were detected in all the samples evaluated. The chemical variability of the essential oils in the sachet samples turned difficult to assess their authenticity. The antioxidant potentials of all essential oils evaluated were much lower than the antioxidant capacities measured for the positive controls of rutin and gallic acid (IC50 = 0.093 mg mL-1 and 0.0085 mg mL-1, respectively). All essential oils analyzed can be classified as cytotoxic agents according to the Artemia salina toxicity test.